Treatment experience of Taiwanese patients with anti‐3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase myopathy. Issue 8 (14th July 2020) - Liang, Wen‐Chen; Wang, Chen‐Hua; Chen, Wan‐Zi; Kuo, Yun‐Ting; Lin, Hsiu‐Fen; Suzuki, Shigeaki; Nishino, Ichizo; Jong, Yuh‐Jyh
Abstract: Immune‐mediated necrotizing myopathy (IMNM) has emerged as a new subgroup of idiopathic inflammatory myopathy in the past decade, associated with the presence of two autoantibodies against signal recognition particle and 3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase (HMGCR). We aim to analyze the clinical, pathological, and imaging phenotypes of the patients with anti‐HMGCR myopathy in our cohort. Five patients with anti‐HMGCR myopathy have been enrolled who were all female; three were pediatric and two were adult patients. The muscle pathology of patients met the diagnostic criteria of IMNM. On muscle magnetic resonance imaging, adductors were earliest affected while lower legs were relatively preserved with highest degree of involvement in medial head of gastrocnemius. In upper extremities, biceps brachii was the most severely involved, followed by triceps. All patients were refractory to steroid mono‐therapy. For pediatric patients, all three patients eventually became responsive to steroid with either intravenous immunoglobulin or rituximab despite variable motor function recovered at present due to different intervention timing. For adult patients, one with statin exposure responded well to steroid and azathioprine use and the motor function returned to the baseline. The other adult patient finally got stabilized and slowly improved with steroid and methotrexate 13 years after the start of therapy. The creatine kinase (CK) levels of all patients were decreased along with clinical severity. In conclusion, muscle imaging might be of help for the diagnosis. Treatment with immuno‐suppressants could be considered together with steroid from the beginning.